Perancangan Media Pembelajaran Gerbang Logika Menggunakan Markerless Berbasis Augmented Reality - Venus Selvita; Putri Mandarani; Eko Kurniawanto Putra; Ganda Yoga Swara; Eva Yulianti (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Logic gate learning is a fundamental topic in digital electronics; however, the learning process is often delivered theoretically with limited visualization of logic gate operations, making it difficult for students to understand the concepts. This study aims to design and develop an Augmented Reality (AR)-based learning media using a markerless approach with the 3D Object Tracking technique on Android devices. The application was developed using the Multimedia Development Life Cycle (MDLC) method, which consists of the stages of concept, design, material collection, development, testing, and distribution. The developed application provides three-dimensional visualization of logic gates, learning materials, interactive simulations, and quizzes. The application quality was evaluated based on the ISO/IEC 25010 standard, covering the aspects of Functional Suitability, Performance Efficiency, Usability, Compatibility, and Portability. The evaluation results showed that the application achieved a score of 100% in the Functional Suitability, Performance Efficiency, Compatibility, and Portability aspects. Meanwhile, the Usability evaluation obtained scores of 86,6% from respondents who had not previously studied logic gates and 89% from those who had, indicating that the application is categorized as highly feasible. Therefore, the developed markerless Augmented Reality-based learning media can serve as an interactive, engaging, and effective learning alternative for improving students' understanding of logic gate concepts.